Exposure to Cyberbullying Victimization and Its Implications for Adolescent Health in the Digital Era - Umar, Zulkifli; Mardahlia, Dewi; Ardan, M (STMIK Widya Cipta Dharma, 2025)
Cyberbullying victimization is a form of technology-based harassment that has been increasing in line with the rising use of social media among adolescents. This phenomenon has implications for both physical and mental health and has the potential to encourage risky behaviors. This study aims to analyze the relationship between social media use, exposure to cyberbullying victimization, and its implications for adolescent health risk behaviors in Samarinda City. The research employed a cross-sectional design involving 393 high school students aged 16–18 years, selected through purposive sampling. Data were collected using a structured questionnaire covering social media use, experiences of harassment, bullying, intimidation, and health risk behaviors. The analysis was conducted using the Partial Least Squares–Structural Equation Modeling (PLS-SEM) approach. The findings revealed that 45% of adolescents had experienced cyberbullying, with verbal harassment, intimidation, and the spread of harmful content as the dominant forms. Furthermore, 35.2% of respondents were identified as engaging in risky behaviors, particularly social media addiction, substance abuse, and risky sexual behavior. The PLS-SEM model demonstrated that social media use was positively associated with harassment, bullying, intimidation, and cyberbullying victimization (p < 0.05). In addition, cyberbullying victimization, harassment, and intimidation significantly contributed to adolescent health risk behaviors, with an R² value of 0.62. Exposure to cyberbullying victimization was proven to have a significant impact on adolescent health risk behaviors. Promotive and preventive interventions involving families, schools, and health services are needed to strengthen adolescent resilience and to create a safe digital ecosystem in the technological era.